2010
DOI: 10.1016/j.otohns.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Utility of elastography for differential diagnosis of benign and malignant thyroid nodules

Abstract: Although elastography can assist in the differential diagnosis of thyroid nodules, its diagnostic performance is not ideal at present. Further improvements in the technique and the diagnostic criteria are necessary for this examination to provide a useful contribution to diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
3
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 19 publications
5
62
3
5
Order By: Relevance
“…However, the optimal strain ratio cut-off values vary among studies. Unlike our results, Xing [29] and his colleagues reported a strain ratio of 3.79 as the cut-off, Kagoya et al [30], reported >1.5 as the cut-off and Ning et al stated 4.2 as the cut-off for predicting malignancy. This variation may be due to difference in the methodology of calculating strain ratios, and difference in the pathology of the nodules included in the study.…”
Section: Variablescontrasting
confidence: 99%
“…However, the optimal strain ratio cut-off values vary among studies. Unlike our results, Xing [29] and his colleagues reported a strain ratio of 3.79 as the cut-off, Kagoya et al [30], reported >1.5 as the cut-off and Ning et al stated 4.2 as the cut-off for predicting malignancy. This variation may be due to difference in the methodology of calculating strain ratios, and difference in the pathology of the nodules included in the study.…”
Section: Variablescontrasting
confidence: 99%
“…Joint analysis of B-mode and strain elastography (qualitative and semiquantitative approach) did not exceed the discriminatory power of B-mode assessment (AUC 0.712 vs. 0.740). This is consistent with the literature [18][19][20]. It may be attributable to the location and neighbourhood of the thyroid on the neck, with location of the lateral lobes in the groove between sternocleidomastoid muscle and trachea, resulting in the oblique movements of the thyroid gland and nodules upon vertical compression with the probe by the operator.…”
Section: Prace Oryginalnesupporting
confidence: 91%
“…Second, not all nodules are amenable to sonoelastography. Sonoelastography cannot be performed on nodules with peripheral rim calcification, nodules with a large cystic component, nodules with a diameter of <5 mm and coalescent nodules (Lyshchik et al, 2005;Rago et al, 2007;Asteria et al, 2008;Dighe et al, 2008;Hong et al, 2009;Rubaltelli et al, 2009;Bojunga et al, 2010;Kagoya et al, 2010). Third, the overall quality of sonoelastography is dramatically affected by the decorrelation noise caused by the out-of-plane motion of the examined lesion under compression and the pulsation of the carotid artery (Lyshchik et al, 2005;Asteria et al, 2008;Rubaltelli et al, 2009;Bojunga et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the neck contains a wide range of structures in relatively narrow compartments. Therefore, elastographic imaging of the thyroid gland will require more training to achieve optimal images for diagnosis (Hong et al, 2009;Kagoya et al, 2010).…”
Section: Discussionmentioning
confidence: 99%